Cigarette smoke modulates binding of the transcription factor MZF1 to the VEGF promoter and regulates VEGF expression in dependence of genetic variation SNP 405. (16th June 2020) - Krüger, Maximilian; Metzger, Carmen; Al‐Nawas, Bilal; Kämmerer, Peer W.; Brieger, Jürgen
Abstract: Background: Vascular endothelial growth factor (VEGF) affects carcinogenesis of the upper aerodigestive tract. Cigarette smoke (CSE) influences VEGF‐gene regulation. The single nucleotide polymorphism +405 G/C (SNP +405 G/C) and the transcriptional factor (TF) myeloid zinc finger 1 (MZF1) are endogenic regulators of the VEGFpromoter as the polymorphism 405 potentially affects binding of the transcription factor MZF1. Therefore, this in vitro study analysed cancer cells of the upper aerodigestive tract after CSE incubation concerning MZF1‐binding specificity and VEGF expression in dependency of VEGF polymorphism +405 G/C compared to wild type (wt). Methods: In human alveolar epithelial‐like type‐II cells (A549) and oral squamous cell cancer cells (HNSCCUM‐02T) SNP +405 G/C‐ and MZF1‐dependent VEGF promoter activity and VEGF expression were analysed by qRT‐PCR and Western blot after incubation with 10% CSE. Temporary knock‐down of MZF1 was performed using siRNA. MZF1 binding was analysed by Co‐Chromatin‐Immunoprecipitation (Co‐ChiP) (each test n = 3). Results: We found a stronger MZF1 binding to VEGF polymorphism 405 in A549 cells ( P  < .05) compared to HNSCCUM‐02T cells ( P  = .02), where MZF1 binding was reduced. MZF1 knock out reduced VEGF promoter activity in HNSCCUM‐02T cells, showing the relevance of the factor for transcriptional activation of the VEGF promoter. Finally, we found that CSE increases promoter activity in both cell lines and no significant differences between the two analysed polymorphisms concerning their activating capacity. Conclusion: In summary, both VEGF promoter polymorphisms are similar effective in terms of transcriptional activity, and MZF1 is a transcriptional activator of VEGF promoter. Moreover, cigarette smoke increases MZF1 binding of VEGF‐promoter and directly affects VEGF‐gene regulation.